THE INFLUENCE OF CONFLICT AND LEADERSHIP STYLE ON THE PERFORMANCE OF PT MARKETING EMPLOYEES. SAPTA SYNERGY SOURCINDO - Nikita Nikita; Meysiana Lindriani (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
In companies, differences of opinion are often deliberately created as one of the strategies of company leaders to make changes in the company. Changes can be made by making or creating a conflict. This study aims to determine the influence of conflict and leadership style in Palembang city. The target of this study is to determine the effect of conflict and leadership style on the performance of employees of PT Sapta Sourcindo in Palembang city. The method that will be used in achieving the objectives of this research is the survey method. Researchers took samples using convenience sampling techniques. The sample criteria distributed were employees of PT. Sapta in Palembang city. Numbering 40 employees. Researchers will ask questions about the conflict and leadership style of PT. Sapta in Palembang city in the form of a questionnaire. The results of this study state that there is a positive and significant influence between conflict and leadership style on the performance of marketing employees at PT Sapta Sinergi Sourcindo in Palembang City.